Geostrategic Significance Of The BeleuliCarvansaray On Trade Routes Of The Lower Amu Darya Region - Djoldasov, A.B. (American Journal Of Social Sciences And Humanity Research, 2026)
This article scientifically examines the geostrategic significance of the Beleuli caravanserai, located on the trade routes of the Lower Amu Darya region, its place in the system of ancient caravan routes, its defensive and defensive architecture, and its role in regional trade and cultural relations. The article highlights the significance of the caravanserai as a trade infrastructure connecting Kazakhstan, Karakalpakstan, and the Caspian region, and analyzes its prospects for modern tourism as a geocultural heritage site.